Safety of Percutaneous Endoscopic Gastrostomy Tubes in Centenarian Patients - Zain A Sobani; Kevin Tin; Steven Guttmann; Anna A Abbasi; Ira Mayer; Yuriy Tsirlin (Clinical Endoscopy, 2018)
Background/Aims Percutaneous endoscopic gastrostomy (PEG) is a relatively safe procedure; however, no study has evaluated the safety of PEG tube placement in patients over the age of 100 years. Methods We conducted a retrospective review of patient records for patients who underwent PEG tube placement. Thirty patients aged 100 years and older were identified and a random sample of 275 patients was selected for comparison. Results The mean age of the patients was 80.6±16.2 years. No procedure-related deaths or major complications were identified; the overall inpatient mortality rate was 7.6%. Minor complications were noted in 4% (n=12) of the patients. Centenarian patients were predominantly female (80% [n=24] vs. 54% [n=147], p=0.006), with a mean age of 100.5±0.9 years. There was no significant difference in procedural success rates (93.3% vs. 97.4%, p=0.222) or inpatient mortality (6.7% [n=2] vs. 7.7% [n=21], p=1.000) between the two groups. However, a higher minor complication rate was noted in the older patients (13.3% [n=4] vs. 2.9% [n=8], p=0.022). Conclusions Success rates, major complications and inpatient mortality associated with PEG tubes in patients aged over 100 years are comparable to those observed in relatively younger patients at our center; however minor complication rates are relatively higher. These findings lead us to believe that PEG tubes may be safely attempted in carefully selected patients in this subset of the population.